Significance of morphology in the systematics of Mesembryanthemaceae : interactive database and illustrated atlas for identification - Van Wyk, Abraham Erasmus (Braam) (University of Pretoria, 2022)
Thesis (DPhil)--University of Pretoria, 2004.